Plasma myoglobin indicates muscle damage associated with acceleration/deceleration during football - Saita, Y.; Hattori, K.; Hokari, A.; Ohyama, T.; Inoue, J.; Nishimura, T.; Nemoto, S.; Aoyagi, S. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Monitoring muscle damage in athletes assists not only coaches to adjust the training workload but also medical staff to prevent injury. Measuring blood myoglobin concentration can help evaluate muscle damage. The novel portable device utilized in this study allows for easy on-site measurement of myoglobin, providing real-time data on the player`s muscle damage. This study investigated the relationship between external load (global positioning system parameters) and internal loads (myoglobin concentration and creatine kinase activity) in 15 male professional football players before and after a match. METHODS: Whole blood samples from participants` fingertips were collected before the match (baseline) and at 2, 16, and 40 h after the match. Myoglobin concentrations were measured using the IA-100 compact immunoassay system. Creatine kinase concentrations were measured in a clinical laboratory, and match loads were monitored using a global positioning system device. RESULTS: The mean myoglobin concentration was significantly higher at 2 h than at the other time points (P<0.05), and decreased to baseline levels within 16 h post-match. The mean creatine kinase concentration increased after the match but did not reach a significant level. Muscle damage monitored by myoglobin after football match-play was strongly associated with acceleration/deceleration metrics rather than the sprint/high-speed running distance. CONCLUSIONS: Our findings indicate that myoglobin is a more sensitive marker of muscle damage than creatine kinase after football match-play. Monitoring myoglobin in athletes can aid in determining their recovery status from the previous training load and help practitioners manage the training load.